513 Clinical Audit Platform for Students (CAPS): A Pilot Study. (12th October 2021) - Hashmi, Y; Kumar, P R; Morad, R; Dewan, V
Abstract: Introduction: Clinical audit projects work to decrease the occurrence of clinical mistakes and ensure current practice is optimal for patients. However, many clinicians are unable to carry out regular audits given their time constraints. Conversely, medical students are often eager to complete audits early in their career to strengthen their portfolios. As such, the clinical audit platform was designed to connect willing supervisors and these medical students. Method: A medical school Trauma & Orthopaedics (T&O) society organised clinical audit teaching sessions for interested students. Allocation of students to project supervisors was based on similar topic interests. There was regular communication to track progress and anonymised feedback forms were distributed to all students and supervisors after the programme. Results: A total of 17 responses were received from the 19 students who were involved in a project. Based on a 5-point Likert scale, students displayed a mean improvement in their understanding of a clinical audit (1.18 ± 1.07, p < 0.001), the confidence to approach a supervisor (1.29 ± 1.21, p < 0.001) and the ability to conduct an audit by themselves in the future (1.77 ± 1.15, p < 0.001). Eagerness to pursue a career in T&O increased from 35.3% to 70.6% of students following the programme. Of the 7 affiliated supervisors, 5 provided feedback and all were happy with the quality of work produced. Conclusions: The platform produced high quality projects which were disseminated both locally and nationally, demonstrating positive collaboration between students and clinicians. We present our findings to encourage similar audit platforms to be adopted at other locations.